2007
DOI: 10.1007/s00216-007-1373-1
|View full text |Cite
|
Sign up to set email alerts
|

Contact angle measurements under thermodynamic equilibrium conditions

Abstract: The precise control of the ambient humidity during contact angle measurements is needed to obtain stable and valid data. For a such purpose, a simple low-cost device was designed, and several modified surfaces relevant to biosensor design were studied. Static contact angle values for these surfaces are lower than advancing contact angles published for ambient conditions, indicating that thermodynamic equilibrium conditions are needed to avoid drop evaporation during the measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…The latter represents the final equilibrium value, after a rapid shift that could be appreciated in the first 30 min of reaction. The pH of the solution after the reaction remained around a value of 5.6, suggesting a ionized state of the surface exposed carboxylic group of adsorbed MUA [29], and in agreement with a measured ζ-potential of -23 AE 3 mV (n ¼ 6). The average hydrodynamic diameters of 27 AE 2 nm (number) and 33 AE 2 nm (intensity) indicates that the modification procedure is consistent with the formation of MUA-capped nanoparticles with no appreciable aggregation (Supplementary Material SM7 Figure S10).…”
Section: Citrate To Mua Ligand Exchangesupporting
confidence: 85%
“…The latter represents the final equilibrium value, after a rapid shift that could be appreciated in the first 30 min of reaction. The pH of the solution after the reaction remained around a value of 5.6, suggesting a ionized state of the surface exposed carboxylic group of adsorbed MUA [29], and in agreement with a measured ζ-potential of -23 AE 3 mV (n ¼ 6). The average hydrodynamic diameters of 27 AE 2 nm (number) and 33 AE 2 nm (intensity) indicates that the modification procedure is consistent with the formation of MUA-capped nanoparticles with no appreciable aggregation (Supplementary Material SM7 Figure S10).…”
Section: Citrate To Mua Ligand Exchangesupporting
confidence: 85%
“…Table 1 summarizes the water contact angle values of the variously functionalized surfaces. The contact angles are in a good agreement with those reported in previous works [ [54] , [55] , [56] , [57] , [58] , [59] ].…”
Section: Resultssupporting
confidence: 91%
“…However, Miyama et al have reported that in general, the static contact angle is greater than the receding and less than the advancing contact angle [27], which is consistent with our results. Nevertheless, slight discrepancies between the measured values and the values reported in the literature could be anticipated as contact angle measurements can be affected by various factors, such as surface roughness and defects [26], ambient humidity [28], and the choice of method [29]. Interestingly, the contact angle of water on DPPTE SAM is of the same magnitude as that on the decanethiol SAM, even though the length of the hydrocarbon chain in DPPTE (Fig.…”
Section: Surface Tension and Contact Angle Measurementsmentioning
confidence: 75%